2003
DOI: 10.1038/nature01531
|View full text |Cite
|
Sign up to set email alerts
|

Cell fusion is the principal source of bone-marrow-derived hepatocytes

Abstract: Evidence suggests that haematopoietic stem cells might have unexpected developmental plasticity, highlighting therapeutic potential. For example, bone-marrow-derived hepatocytes can repopulate the liver of mice with fumarylacetoacetate hydrolase deficiency and correct their liver disease. To determine the underlying mechanism in this murine model, we performed serial transplantation of bone-marrow-derived hepatocytes. Here we show by Southern blot analysis that the repopulating hepatocytes in the liver were he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
1,068
10
17

Year Published

2004
2004
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,477 publications
(1,129 citation statements)
references
References 26 publications
24
1,068
10
17
Order By: Relevance
“…Tanimizu et al [54] have selected such cells on the basis of expression of Dlk, a type1 membrane protein that has six EGF-like repeats in its extracellular domain, and Dlk combined with immunopositivity for AFP, albumin, E-cadherin and Liv2 (a molecule only expressed at ED 9.5-12.5) has selected for a Stem cells in liver regeneration, fibrosis and cancer 287 population capable of an 80% replacement of the DPPIV-deficient mouse liver [55]. The key to the success of the transplantation was again that the mice had been pre-treated with retrorsine (blocking indigenous hepatocyte replication) and given courses of hepatocyte-destroying CCl 4 , both before and after cell transplantation. Clonogenic cells have also been isolated by Suzuki et al [56] from fetal mouse liver (ED13.5), on the basis of expressing the integrins α6 (CD49f) and β1 (CD29) but not c-kit, CD45 or Ter119 (erythroid precursor antigen).…”
Section: Mr Alison Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Tanimizu et al [54] have selected such cells on the basis of expression of Dlk, a type1 membrane protein that has six EGF-like repeats in its extracellular domain, and Dlk combined with immunopositivity for AFP, albumin, E-cadherin and Liv2 (a molecule only expressed at ED 9.5-12.5) has selected for a Stem cells in liver regeneration, fibrosis and cancer 287 population capable of an 80% replacement of the DPPIV-deficient mouse liver [55]. The key to the success of the transplantation was again that the mice had been pre-treated with retrorsine (blocking indigenous hepatocyte replication) and given courses of hepatocyte-destroying CCl 4 , both before and after cell transplantation. Clonogenic cells have also been isolated by Suzuki et al [56] from fetal mouse liver (ED13.5), on the basis of expressing the integrins α6 (CD49f) and β1 (CD29) but not c-kit, CD45 or Ter119 (erythroid precursor antigen).…”
Section: Mr Alison Et Almentioning
confidence: 99%
“…More severe liver injury, particularly longstanding iterative injury (eg chronic viral hepatitis) or when replicative senescence ensues (eg steatohepatitis), activates a facultative stem cell compartment located within the intrahepatic biliary tree, giving rise to cords of bipotential transit amplifying cells (named oval cells in rodents and hepatic progenitor cells in man) that can ultimately differentiate into hepatocytes and biliary epithelial cells [2]. A third population of stem cells with hepatic potential resides in the bone marrow; these stem cells usually make little contribution to regeneration but, after fusing with metabolically defective hepatocytes, can be reprogrammed to contribute in a major way to restoring liver function [3][4][5]. Mesenchymal cells from bone marrow and other locations, particularly adipose tissue, appear to be the most suitable extra-hepatic candidate cells for hepatic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this premise, hematopoietic stem cells (HSCs) have been shown to transdifferentiate into cells of the hepatocytic lineage in both rodents and humans [16][17][18][19][20][21][22][23]. However, these findings have been challenged by studies showing that cell fusion rather than transdifferentiation of HSCs is involved in regeneration [24,25] and that bone marrow (BM) does not contribute as source of expanding oval cells [26]. Thus, it remains to be determined to what degrees HSCs as opposed to endogenous-derived liver oval cells participate in regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…This process is very controversial since the dogma of development is based on the commitment of cells to specific fate and it is not clear how the cells expand their potential and change their fates. In later reports, it was shown that this process of transdifferentiation may be misinterpreted because of cell fusion between the transplanted cells and the native hepatocytes [Vassilopoulos et al, 2003;Wang et al, 2003]. ES cells are self-renewing pluripotent cells capable of differentiating into derivatives of the three germ layers.…”
Section: Liver Pathologies and Therapiesmentioning
confidence: 99%